Zur bleibenden Bedeutung - Dietrich Benner (Jesuit University Ignatianum in Krakow, 2017)
Educational teaching is an inventive idea of combining upbringing and education, which was ﬁ rst developed by Johann Friedrich Herbart, a 19th-century German philosopher and pedagogue. He presented it as one of the three stages of the spiritual and intellectual development of a pupil (apart from "ruling the children" and management). Herbart's concept spread soon and found application primarily in the European educational system in the period of the so-called Herbartianism - since 1850s until 1920s. Also in our times the need for upbringing at school is being discussed, though not in the context of Herbart. Dietrich Benner does not aim at coming back to history, but reading of the Herbartian idea in the light of modern didactics. In the ﬁ rst chapter the author indicates two tasks for educational teaching: broadening pre-scientiﬁ c experience and communion with other people. In the "artiﬁ cial" conditions of school education pupil's popular experience should be enriched with science and art, and communion - with politics and religion. The two triads presented (experience - science - art and communion - politics - religion) make the six "interests" of the famous Herbartian idea of versatile training of interests. The second chapter displays three beneﬁ ts arising from the "artiﬁ cial" (i.e. school) broadening of experience and communion. According to Benner these are: thematic, methodological and institutional openness. In the next chapter the author presents a modern interpretation of "the stages of educational teaching".